The Urgency of Regulating Air Rights and Transfer of Development Rights (TDR) in Indonesia’s Land Law System: A Jakarta Case Study - Mohammad Rafsanjani Akbar; Ghazi Ahmad Tijani (Graha Primera Saintifika, 2025)
Jakarta faces severe land constraints due to its high population density (over 14,000 people per sq km). This pressure has driven vertical development and innovative urban projects, highlighting the urgency for clear legal frameworks on air rights and Transfer of Development Rights (TDR). Air rights refer to the ability to use or develop the space above land, while TDR is a planning tool allowing the transfer of unused building potential from one parcel to another. Currently, Indonesia’s land law system lacks explicit regulations for these concepts, creating legal uncertainties and limiting urban planners’ flexibility. This research examines the need for formalizing air rights and TDR in Indonesian agrarian law, using Jakarta as a case study. A comparative analysis with practices in the United States and Singapore is conducted to glean insights into how robust air rights and TDR regimes can guide sustainable urban growth. Findings indicate a significant regulatory gap: existing laws (e.g., Basic Agrarian Law of 1960) do not accommodate separate airspace utilization or development rights trading. International examples demonstrate that well-regulated air rights and TDR mechanisms help preserve essential spaces (farmland, heritage sites) while promoting strategic densification. The study concludes with recommendations (ius constituendum) for Indonesian legal reforms to integrate air rights and TDR, ensuring Jakarta and other cities can optimize vertical space and direct development in a controlled, equitable manner.